2020
DOI: 10.9734/ajpas/2020/v7i130171
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Fluctuation of the Price of Crude Oil in Nigeria Using ARCH, ARCH-M Models

Abstract: As a mono-product economy, where the main export commodity is crude oil, volatility in oil prices has implications for the Nigerian economy and, in particular, exchange rate movements. The latter is particularly important due to the twin dilemma of being an oil exporting and oil-importing country, a situation that emerged in the last decade. The study examined the effects of oil price volatility, demand for foreign exchange, and external reserves on exchange rate volatility in Nigeria using monthly data over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This is as a result of high fluctuations in crude oil prices. Furthermore, the 10 month ahead forecast of the monthly crude oil price returns using ARIMA (2, 0, 5)-GARCH (1,4) showed an oil with an unstable monthly price movement. Fig.…”
Section: Discussion Of Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…This is as a result of high fluctuations in crude oil prices. Furthermore, the 10 month ahead forecast of the monthly crude oil price returns using ARIMA (2, 0, 5)-GARCH (1,4) showed an oil with an unstable monthly price movement. Fig.…”
Section: Discussion Of Resultsmentioning
confidence: 98%
“…Consequently, the ARIMA (2, 0, 5) was used as the conditional mean for the GARCH modeling of Nigeria crude oil price volatility within the period under consideration. It was observed that ARIMA (2, 0, 5)-GARCH (1,4) performed better than other ARIMA (2,0,5)-GARCH models with a minimum AIC of 7.1855. Also, the crude oil price return showed a persistent high volatility, this makes it difficult for Nigerian government to predict and plan her revenue from the sale of crude oil.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation